1986
DOI: 10.1002/j.1460-2075.1986.tb04297.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of human granulocyte colony-stimulating factor (G-CSF).

Abstract: A colony‐stimulating factor (CSF) has been purified to homogeneity from the serum‐free medium conditioned by one of the human CSF‐producing tumor cell lines, CHU‐2. The molecule was a hydrophobic glycoprotein (mol. wt 19,000, pI = 6.1 as asialo form) with possible O‐linked glycosides. Amino acid sequence determination of the molecule gave a single NH2‐terminal sequence which had no homology to the corresponding sequence of the other CSFs previously reported. The biological activity was apparently specific for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
68
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(71 citation statements)
references
References 53 publications
2
68
0
1
Order By: Relevance
“…G-CSF is a primary cytokine capable of stimulating the proliferation and activation of neutrophils [15]. An elevated serum level of G-CSF (74 pg·mL -1 ) was also observed in our patient (table 1), compared with a concentration of 13.8±7.7 pg·mL -1 measured in 116 normal Japanese individuals [8].…”
Section: Discussionsupporting
confidence: 71%
“…G-CSF is a primary cytokine capable of stimulating the proliferation and activation of neutrophils [15]. An elevated serum level of G-CSF (74 pg·mL -1 ) was also observed in our patient (table 1), compared with a concentration of 13.8±7.7 pg·mL -1 measured in 116 normal Japanese individuals [8].…”
Section: Discussionsupporting
confidence: 71%
“…We have previously reported that the resistance of such neutropenic mice to infection was restored to normal levels by subcutaneous (s.c.) injections of human granulocyte colony-stimulating factor (G-CSF) derived from human squamous carcinoma CHU-2 cells (11). The G-CSF used in those experiments was a purified native factor (13). The gene encoding human G-CSF has recently been cloned and recombinant G-CSF (rG-CSF) can be produced by transfecting the gene into Chineses hamster ovary (CHO) cells (12).…”
mentioning
confidence: 99%
“…Following the purification of human G-CSF from tumor cell lines (16) and its utilization for immunoperoxidase staining of paraffin-embedded sections (17), several G-CSF-secreting pancreatic carcinomas have been confirmed using immunohistochemistry (6). The diagnostic criteria for G-CSF-producing tumors are as follows: i) Extreme leukocytosis, ii) elevated G-CSF activity, iii) a decreased white blood cell count following tumor resection, or iv) proof of G-CSF production in the tumor (9).…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF functions as not only a hematopoietic growth factor but also as an autocrine growth factor associated with the proliferation of tumor cells (19,20). G-CSF released by tumor cells may bind to G-CSF receptors in the tumor cells, triggering proliferation, invasion, migration via an autocrine mechanism, and the transformation of the epithelial elements into a more immature or high-grade phenotype (16,19). Regardless of the therapeutic efforts, the prognosis of patients G-CSF-producing pancreatic tumors is extremely poor, which is supported by the fact that all referred cases, regardless of surgical treatment or chemotherapy, succumbed to disease within 8 months of the initial consultation (12).…”
Section: Discussionmentioning
confidence: 99%